Interaction between tobacco smoking and hepatitis B virus infection on the risk of liver cancer in a Chinese population - Liu, Xing; Baecker, Aileen; Wu, Ming; Zhou, Jin‐Yi; Yang, Jie; Han, Ren‐Qiang; Wang, Pei‐Hua; Jin, Zi‐Yi; Liu, Ai‐Min; Gu, Xiaoping; Zhang, Xiao‐Feng; Wang, Xu‐Shan; et al. (International journal of cancer, 2018)
Although tobacco smoking has been reported as a risk factor for liver cancer, few studies have specifically explored the association among Chinese females and the potential interaction between smoking and other risk factors. A population‐based case–control study was conducted and 2,011 liver cancer cases and 7,933 healthy controls were enrolled in Jiangsu, China from 2003 to 2010. Epidemiological data were collected, and serum hepatitis B surface antigen (HBsAg) and anti‐HCV antibody were measured. Unconditional logistic regression was used to examine association and potential interaction, while semi‐Bayes (SB) method was employed to make estimates more conservative. The prevalence of serum HBsAg positivity was 43.2% among cases and 6.5% among controls. The adjusted odds ratios (OR) for ever smoking were 1.62 (95% confidence interval [CI]: 1.33–1.96) among male and 0.82 (95% CI: 0.53–1.26) among female. Age at first cigarette, duration of smoking and pack‐years of smoking were all significantly associated with liver cancer among men. Compared to HBsAg‐negative never smokers, the adjusted ORs were 1.25 (95% CI: 1.03–1.52) for HBsAg‐negative ever smokers, 7.66 (95% CI: 6.05–9.71) for HBsAg‐positive never smokers, and 15.68 (95% CI: 12.06–20.39) for HBsAg‐positive ever smokers. These different odds ratios indicated super‐additive (RERI: 7.77, 95% CI: 3.81–11.73) and super‐multiplicative interactions (ROR: 1.64, 95% CI: 1.17–2.30) between hepatitis B virus (HBV) infection and tobacco smoking. Most associations and interactions detected remained statistically significant after SB adjustments. Tobacco smoking and HBV infection positively interact in the development of liver cancer. What's new? Tobacco smoking is a major risk factor for various cancer types, including liver cancer. Half of new liver cancer cases reported annually worldwide occur in China, where the prevalence of smoking and hepatitis B virus (HBV) infection are high. Here, associations between tobacco smoking and liver cancer and interactions between smoking and other risk factors were examined in a Chinese population. Significant interactions were detected between smoking and HBV infection. Analyses by gender indicated that associations between smoking and liver cancer existed primarily among men, who were more likely than women to have been ever smokers or current smokers.